The Effect of Leverage, Institutional Ownership, and Liquidity on Company Value in Infrastructure Companies Listed on The Indonesian Stock Exchange (Period 2020-2022) - Kurnia Putri; I Gusti Ngurah Bagus Gunadi; Agus Wahyudi Salasa Gama (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
This study aims to examine the effect of leverage, institutional ownership, and liquidity on company value. The population in this study consists of infrastructure companies listed on the Indonesia Stock Exchange during the observation period of 2020-2022. The sampling technique used is purposive sampling, which is a sampling technique based on criteria determined by the researcher. Based on the sample selection criteria, 40 companies and 120 samples were obtained. The data analysis technique used was multiple linear regression analysis, which was processed using the SPSS version 23 program. The results of this study indicate that leverage and liquidity do not affect company value, while institutional ownership has a positive effect on company value.